2011
DOI: 10.1542/peds.2010-3242
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin in Neonates With Rhesus Hemolytic Disease: A Randomized Controlled Trial

Abstract: Prophylactic IVIg does not reduce the need for exchange transfusion or the rates of other adverse neonatal outcomes. Our findings do not support the use of IVIg in neonates with rhesus hemolytic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 29 publications
5
64
1
3
Order By: Relevance
“…In a follow-up study of a randomized controlled trial conducted at our center, we found that the neurodevelopmental outcome in children treated with intravenous immunoglobulins for HDFN was not different from children treated with placebo [32,99]. At a median age of 4 years, NDI was detected in 3% in both the IVIG (1/34) and placebo (1/32) group.…”
Section: Long-term Outcome After Immunoglobulinsmentioning
confidence: 83%
See 2 more Smart Citations
“…In a follow-up study of a randomized controlled trial conducted at our center, we found that the neurodevelopmental outcome in children treated with intravenous immunoglobulins for HDFN was not different from children treated with placebo [32,99]. At a median age of 4 years, NDI was detected in 3% in both the IVIG (1/34) and placebo (1/32) group.…”
Section: Long-term Outcome After Immunoglobulinsmentioning
confidence: 83%
“…In our center, the exchange transfusion rate in HDFN dropped from approximately 70% before 2005 [33] to approximately 15% thereafter [32]. This reduction was due to the implementation of a more restrictive guideline for exchange transfusions in terms of bilirubin cutoff values, especially by introducing cutoff values for different risk groups, compared to the more liberal guideline used at our center before 2005.…”
Section: Exchange Transfusionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although the use of intravenous gamma-globulin has been shown, in several randomized controlled trials, to reduce the need for exchange transfusions in both Rh and ABO hemolytic disease, 53-55 a recent study of intravenous gamma-globulin administration to infants with severe Rh hemolytic disease did not confirm these findings. 56 It is possible that the severity of hemolysis has a role in determining the response to intravenous gamma-globulin. 57 …”
Section: Hemolytic Diseasementioning
confidence: 99%
“…However low dose IVIG found to be less effective in avoiding exchange transfusion in rhesus hemolytic disease of the newborn [14]. Apart from these results, SmitsWintjen concluded that prophylactic treatment with IVIG in rhesus hemolytic disease did not reduce the need for exchange transfusion or adverse neonatal outcomes [15]. Most of these studies were done in patients with rhesus hemolytic disease of the newborn, there are small number of patients with ABO hemolytic disease, it is not clear that IVIG is efficacious in ABO hemolytic disease of newborns so routine use of IVIG is still controversial because its efficacy has not been definitely demonstrated.…”
Section: Resultsmentioning
confidence: 98%